Enhanced Production of β-Caryophyllene by Farnesyl Diphosphate Precursor-Treated Callus and Hairy Root Cultures of Artemisia vulgaris L. - Balasubramani, Sundararajan; Ranjitha Kumari, B. D.; Moola, Anil Kumar; Sathish, D.; Prem Kumar, G.; Srimurali, S.; Babu Rajendran, R. (Frontiers in Plant Science, 2021)
Artemisia vulgaris L. produces a wide range of valuable secondary metabolites. The aim of the present study is to determine the effects of various concentrations farnesyl diphosphate (FDP) on β-caryophyllene content in both callus and hairy root (HR) cultures regeneration from leaf explants of A. vulgaris L. Murashige and Skoog (MS) medium supplemented with various concentrations of 2,4-dichlorophenoxyacetic acid (2,4D; 4–13 µM), α-naphthaleneacetic acid (NAA; 5–16 µM), and FDP (1 and 3 µM) were used for callus induction and HR regeneration from leaf explants of A. vulgaris L. In this study, precursor-treated (2,4D 13.5 µM + FDP 3 µM) callus displayed highest biomass FW/DW: 46/25 g, followed by (NAA 10.7 µM + FDP 3 µM) with FW/DW: 50/28 g. Two different Agrobacterium rhizogenes strains (A4 and R1000) were evaluated for HR induction. The biomass of HRs induced using half-strength MS +B5 vitamins with 3 µM FDP was FW/DW: 40/20 g and FW/DW: 41/19 g, respectively. To determine β-caryophyllene accumulation, we have isolated the essential oil from FDP-treated callus and HRs, and quantified β-caryophyllene using gas chromatography-mass spectrometry (GC-MS). The highest production of β-caryophyllene was noticed in HR cultures induced using A¬4 and R1000 strains on half-strength MS medium containing 3 µM FDP, which produced 2.92 and 2.80 mg/mL β-caryophyllene, respectively. The optimized protocol can be used commercially by scaling up production of a β-caryophyllene compound in short span of time.